Learning Three-Dimensional Shapes in Geometry Using Mobile-Based Augmented Reality - Rohendi, D; Wihardi, Y (International journal of interactive mobile technologies, 2020)
Learning three-dimensional shape of geometry is important for improving students’ spatial abilities. However, the concept of three-dimensional shape is still considered as one of difficult subject matters for teacher to teach and for student to understand in Indonesia. Therefore, it is necessary to find an alternative way that can allow teachers and students to easily understand some concepts of geometry.  In this research, we try to implement mobile-based augmented reality in presenting three-dimensional geometry materials to help teachers and students of junior high school in Bandung, Indonesia.  The results show that by using mobile based augmented reality, teachers can teach three dimensional shape of geometry clearly and students could understand the concept of three-dimensional shape of geometry faster. In addition, students can learn the concept of geometry comprehensively through geometry objects that can be seen from all points of view and students' spatial activities are increased